(untitled) (Jurnal Pembangunan Sosial, 2013)
The purpose of this study is to explore students’ knowledge, resources and experiences of sexuality; and to examine whether there were differences of the students’ knowledge, resources and experiences of sexuality based on the demographic factors. This study was conducted in a school in the northern region of Malaysia, involving 414 students, using a cross-sectional survey technique. The results indicate that the students’ level of knowledge is at a moderate level. There was no significant difference of knowledge level between male and female students. Among the sources that the students refer to for sexuality information were majorly friends, television/movies and the internet. The most frequently reported sexual experiences were watching pornographic movies or videos, dating and reading pornographic materials. The findings of this study have identified the issues and the needs of Malaysian youngsters regarding sexuality, as well as inputs regarding the role of the family and to the related agencies to improve policies regarding the family and the implementation of educational programs on sexuality and preventive programs for social problems among students and adolescents.